2017
DOI: 10.1186/s40709-017-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey of methods and tools to detect recent and strong positive selection

Abstract: Positive selection occurs when an allele is favored by natural selection. The frequency of the favored allele increases in the population and due to genetic hitchhiking the neighboring linked variation diminishes, creating so-called selective sweeps. Detecting traces of positive selection in genomes is achieved by searching for signatures introduced by selective sweeps, such as regions of reduced variation, a specific shift of the site frequency spectrum, and particular LD patterns in the region. A variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 94 publications
5
106
0
Order By: Relevance
“…We first investigated the shape of the site frequency spectrum (SFS), calculating the folded SFS using realSFS (part of the angsd package). In the absence of strong demographic changes or selection, we would expect the SFS to follow an exponential decrease (see e.g., Li et al, ; Pavlidis & Alachiotis, ) and indeed that was what we found. Furthermore, the shape of the SFS can indicate whether the amount of SNP data will be sufficient and whether the data show any signatures of selection or demographic effects (e.g., based on the amount of SNPs with medium allele frequencies).…”
Section: Methodssupporting
confidence: 84%
“…We first investigated the shape of the site frequency spectrum (SFS), calculating the folded SFS using realSFS (part of the angsd package). In the absence of strong demographic changes or selection, we would expect the SFS to follow an exponential decrease (see e.g., Li et al, ; Pavlidis & Alachiotis, ) and indeed that was what we found. Furthermore, the shape of the SFS can indicate whether the amount of SNP data will be sufficient and whether the data show any signatures of selection or demographic effects (e.g., based on the amount of SNPs with medium allele frequencies).…”
Section: Methodssupporting
confidence: 84%
“…The simulations were performed using the PolySim software, which takes into account the organism's polyploidy and self-pollination. Simulation can offer a more precise detection for the significance threshold than the commonly used outlier approaches (Pavlidis & Alachiotis, 2017).…”
Section: Amplicon Resequencingmentioning
confidence: 99%
“…These characteristics are illustrated in Fig. and have been extensively reviewed elsewhere , so we do not devote space to considering their basis here, but do discuss the evidence for selection for each gold standard.…”
Section: Gold Standard Examples Of Classic Selective Sweeps In Humansmentioning
confidence: 99%
“…More recently, the availability of population‐scale genomic data and appropriate statistical tests have allowed the signatures of classic sweeps to be detected in the genome independently of any understanding of the corresponding phenotype or selective force. Thus, there are now vast catalogues of candidate classic sweeps requiring association with their underlying biology .…”
mentioning
confidence: 99%